A new and benign hegemon on the horizon? The Chinese century and growth in the Global South - Tams NguyenHuu; Deniz Dilan Karaman Örsal (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
The authors investigate how the Global South's gross domestic product (GDP) is impacted by trade with China. While the current literature on the growth impacts of trade (by leading partner countries) often neglects the properties of macro panel data, such as cross-sectional dependence, heterogeneity and structural breaks, their models take these features into account. Their empirical results based on 22 major developing countries from 2000Q1 to 2016Q4 identify positive contributions of imports from China to GDP in the studied sample, although these effects are smaller compared to imports from other emerging and developing economies (excluding China) (EME) and advanced economies (AdE). The authors also show that, in contrast with considerable impacts of exports to EME and AdE, exports to China have limited effects on the growth of its partners. However, the global financial crisis marks a turning point of China's role as a major driver of growth in the South. Namely, while the positive growth effects of trade with China after the global crisis are on the rise, the opposite is true for EME and AdE. Examining the effects by individual countries, the authors present that the distance between China and its partners, economic and institutional development levels of its partners are almost irrelevant to the contributions of imports from China to its partners' growth. Based on these findings they provide some important policy recommendations for the economies of the Global South.
http://dx.doi.org/10.7910/DVN/OO8CUQ
Keywords: C23; F43; O4; 330; China; growth; developing and emerging economies; international trade; panel data econometrics; cross-sectional dependence